Optimal routing and frame distribution assignment problem in the integrated services digital network - Grzech, Adam; Kasprzak, Andrzej (1953- ) (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, the optimal routing and frames distribution assignment problem in Integrated Services Digital Network (ISDN) is considered. The problem consists of simultaneously finding the routes for both voice and data traffic and the distribution of frames between voice and data traffics which minimize the total average delay per packet such that the traffic requirements are satisfied. The problem presented here is the nonlinear mixed-integer programming problem.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka